Violence and Aggression in Psychology: A Multidimensional Theoretical and Analytical Study (Comprehensive Journal of Science, 2025)
This research aims to provide a theoretical and analytical reading of the concepts of violence and aggression within the field of psychology. It achieves this by clarifying these concepts, uncovering the factors and causes that explain them, and reviewing the most significant psychological theories that have addressed aggressive behavior. The ultimate goal is to reach a comprehensive understanding that allows for the interpretation of such behavior and the mitigation of its spread within society.The research concluded with several key findings, notably that violence and aggression are complex psychological phenomena arising from the interaction of multiple factors. The results also demonstrated a distinction between the two concepts: aggression is considered a broader term, whereas violence represents a more intense and extreme form of it. Furthermore, the findings indicated that various psychological theories—including psychoanalysis, behaviorism, frustration-aggression theory, and social learning theory—provide integrated explanations for understanding these behaviors.the study’s recommendations emphasized that the prevention of violence necessitates early educational and psychological intervention. This approach should be grounded in sound upbringing and the reinforcement of self-control skills.